Rapid Genomic Evolution Drives the Diversification of Male Reproductive Genes in Dung Beetles. (28th July 2021) - Mrinalini,; Koh, Cho Yeow; Puniamoorthy, Nalini
Abstract: The molecular basis for the evolution of novel phenotypes is a central question in evolutionary biology. In recent years, dung beetles have emerged as models for novel trait evolution as they possess distinct precopulatory traits such as sexually dimorphic horns on their head and thorax. Here, we use functional and evolutionary genomics to investigate the origins and the evolution of postcopulatory reproductive traits in male dung beetles. Male ejaculates that underlie postcopulatory sexual selection are excellent candidates to study novel trait evolution as they are complex, fast evolving, and often highly divergent in insects. We assemble de novo transcriptomes of male accessory glands and testes of a widespread dung beetle, Catharsius molossus, and we perform an evolutionary analysis of closely and distantly related insect genomes. Our results show there is rapid innovation at the genomic level even among closely related dung beetles. Genomic expansion and contraction drive the divergence of male reproductive traits and their functions. The birth of scores of completely novel reproductive genes is reinforced by the recruitment of these genes for high expression in male reproductive tissues, especially in the accessory glands. We find that male accessory glands of C. molossus are specialized for secretory function and express female, egg, and embryo-related genes as well as serine protease inhibitors, whilst the testes are specialized for spermatogenesis and sperm function. Finally, we touch upon putative functions of these evolutionary novelties using structure-function analysis as these proteins bear no homology to any other known proteins.